Developing an interactive games of information management education for online distance learning / Suhaida Halamy, Nurfaizah Kamarudin and Mohsinin Mohsin - Halamy, Suhaida; Kamarudin, Nurfaizah; Mohsin, Mohsinin (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
Gamification has progressively gained popularity in higher education as a valuable complement to the breadth of available learning tools for academicians and students. Plausibly, this is due to the nature of the digital native generation, who are more likely to be interested in educational technologies. The purpose of the study is to develop an Interactive Games of Information Management Education that fosters information literacy and cataloguing skills for information management students. It is a self-learning game for academicians and students that aims to improve educational quality in entertaining ways. This study used a few website applications to design the course content with game elements that innovate the teaching and learning method. An online survey was conducted to examine students’ perception of online interactive game-based learning. A total of 46 students of a public higher learning institution participated in the survey. Based on the frequency analysis, it was found that students’ self-efficacy in information literacy and cataloguing skills increased due to the game’s gamified learning approach. In general, most of the students surveyed have a favourable opinion after experiencing the Interactive Games of Information Management Education for their learning activities. Among others, they agreed that the Interactive Games of Information Management Education provide an effective and enjoyable online learning environment. Additionally, students believed that gamification would benefit them in gaining a better knowledge of the course materials.